Establishment and characterization of a carcinoma-associated fibroblast cell line derived from a human salivary gland adenoid cystic carcinoma. (1st January 2018) - Kong, Jing; Zhao, Han; Shang, Qianhui; Ma, Zhifei; Kang, Ni; Tan, Junling; Ahmed Ibrahim Alraimi, Hyat; Liu, Tingjiao
Abstract: Salivary gland adenoid cystic carcinoma (SACC) is one of the most common malignancies in the oral and maxillofacial region. Carcinoma-associated fibroblast (CAF) is an important component in the tumor microenvironment and participates in SACC progression. In this study, we established a CAF cell line derived from a human SACC and named it CAF-SA. It was identified that CAF-SA expressed typical CAF biomarkers. Then, we studied the cellular communications between CAF-SA, tumor cells and endothelial cells. It was found that CAF-SA promoted the migration, invasion, and proliferation of SACC tumor cells in vitro . In addition, tube formation by endothelial cells was enhanced by CAF-SA. In vivo experiment showed that SACC cells formed larger xenografts in nude mice when they were transplanted with CAF-SA. Overall, we demonstrated that CAF-SA exhibited the most important defining feature of CAF by promoting cancer progression.